Cover page (Discussion Papers, 1999)
The present volume is a collection of studies summarizing the research findings of Polish and Hungarian researchers on the regional aspects of the preparation for EU accession of the two former members of the “Eastern bloc”. The key papers of the volume focus on the 1996 Regional Development Act and on the newly-introduced administrative division of Poland. The common problems of transport and migration link the two studies that follow, both written by Polish researchers. On the topic of the elements which differentiate the Hungarian settlement network, the role of the banking system and the first result of a factorial analysis are presented. The volume contains an introduction to electoral geography in both countries. Polish agriculture is analysed from the perspective of the changing spatial and ownership structures, while Hungarian countryside is represented by studies on second homes and on small region development strategies.